(untitled) (Raíces: Revista de Ciencias Sociales y Políticas, 2023)
This article analyses the logic of healing practices from the narrative of ritual specialists. The research focuses on the Mixteca Alta, in the highlands of Oaxaca, Mexico. It contrasts the primordiality of traditional medicine with current sociocultural practices that open the door to the multiplicity of the mixtec world. The stories are known and disseminated because with them, the ritual specialist reaffirms the recognition of their healing and divinatory capacities. Cosmological analogies are woven (with ethnographic support) that combine the richness of the story with the ritual acts that involve balance and instability (emotional and bodily), health and illness, and ideas about good and evil. The text bets on a vernacular intellectuality that supports the core of the ethnographic data. The story of Grandmother Ñu, the “Goddess of traditional medicine”. A ritual agent that faces the skills of the Sun, the Moon, the deer and any inhabitant who is involved in their actions. The research weaves cosmological analogies or analogical figures because the richness of the story is contrasted with the ritual practices that involve balance and instability or the images that encapsulate ideas about health and disease.